KUALITAS PELAYANAN PERAWAT DI RUANG MEDIKAL BEDAH RUMAH SAKIT SANTA ELISABETH MEDAN - Pomarida Simbolon; Samfriati Sinurat (Politeknik Kesehatan Kemenkes Sorong, 2021)
ABSTRACT Good nurse performance is a guarantee of the quality of health services provided to patients, both sick and healthy. In improving the quality of health services, the performance of a nurse must be high. This study aims to determine the service quality of nurses in the medical-surgical room at Santa Elisabeth Hospital Medan in 2020. The design of this research is descriptive. The sample in the study amounted to 30 people. The research instrument used a questionnaire. Data were analyzed univariately. The results of the study obtained that the quality of nurse service from five dimensions showed that the majority of nurses had responsiveness, assurance, empathy in each good category, 30 people (100%), and reliability, tangibility in each good category as many as 29 people (96.7%). Nurses are expected to be able to maintain and improve the quality of nursing services well. Keywords: Quality of Nurse Services ABSTRAK Kinerja perawat yang baik merupakan jaminan kualitas pelayanan kesehatan yang diberikan kepada pasien baik yang sakit maupun sehat. Dalam meningkatkan kualitas pelayanan kesehatan kinerja seorang perawat haruslah tinggi. Penelitian ini bertujuan untuk mengetahui kualitas pelayanan perawat di ruang medikal bedah Rumah Sakit Santa Elisabeth Medan Tahun 2020. Rancangan penelitian deskriptif. Sampel dalam penelitian berjumlah 30 orang. Instrumen penelitian menggunakan kuesioner. Data dianalisis secara univariat. Hasil penelitian diperoleh kualitas pelayanan perawat dari lima dimensi menujukkan mayoritas perawat memiliki responsiveness, assurance, emphaty masing-masing kategori baik 30 orang (100%), dan reliability, tangibility masing-masing kategori baik sebanyak 29 orang (96,7%). Diharapkan perawat mampu mempertahankan dan meningkatkan kualitas pelayanan perawat dengan baik. Kata Kunci : Kualitas Pelayanan Perawat